Quality assurance in company-based practice : planning and structuring of in-company training by way of the example of the occupation of office manager - Sabbagh, Helena [Verfasser]; Biebeler, Hendrik [Verfasser] (Bundesinstitut für Berufsbildung, 2025)
"The present study looks at the instruments and procedures deployed by companies to ensure successful training in the occupation of office manager. The investigation facilitates an insight into the specific design and use of planning and structural tools in training practice. Alongside the mandatory elements of the company training plan and the report booklet, these include further voluntary evaluation and feedback measures. 238 telephone-based interviews with training management departments and 13 company case studies relating to the occupation of office manager were evaluated in the study. The three areas of training - the crafts, trade and industry and the public sector - were compared with one another." (Editor, BIBB-Doku)
Keywords: S 6.4.3.5 Bürofach-, Bürohilfskräfte; S 2.2.2 Regelung der betrieblichen Ausbildung; L 1.2.2 Betriebliche Ausbildungsorganisation; L 6.2 Qualitätsmanagement/Qualitätssicherung; 370; Betriebliche Berufsausbildung; Kaufmann für Büromanagement; Ausbildungsplanung; Ausbildungskonzeption; Ausbildungsnachweis; Qualitätssicherung; Ausbildungsbereich; Vergleich; Fallbeispiel; Befragung